2013
DOI: 10.1002/er.3058
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparative study of heat pipe performance using CuO and TiO2nanofluids

Abstract: SUMMARY In recent years, developing an energy efficient conventional heat pipe is more important because of the development of electronics and computer industries. To enhance the thermal performance of heat pipe, different nanofluids have been widely used. In this paper, an experimental investigation of heat transfer performance of heat pipe has been conducted using three different working fluids such as DI water, CuO nanofluid and TiO2 nanofluid. The heat pipe used in this study is made up of copper layered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In recent years, thermophysical properties of coolant are improved by the addition of nanosized particles, and this new coolant is known as nanofluid. The nanofluids found to have applications in heat transfer devices, 3,4 energy devices, 5,6 and solar energy systems. [7][8][9] As the present study deals with minichannel heat sinks, the literature on minichannel heat sinks utilizing nanofluids is reviewed herein.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, thermophysical properties of coolant are improved by the addition of nanosized particles, and this new coolant is known as nanofluid. The nanofluids found to have applications in heat transfer devices, 3,4 energy devices, 5,6 and solar energy systems. [7][8][9] As the present study deals with minichannel heat sinks, the literature on minichannel heat sinks utilizing nanofluids is reviewed herein.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable experimental studies have been accomplished to monitor the performance of the thermosiphon in different working conditions. Manimaran et al 14 utilized a copper heat pipe with two layers of mesh filament to enhance its performance. Their experimental results indicated that the optimum performance was achieved at a fill ratio of 0.75.…”
Section: Introductionmentioning
confidence: 99%
“…When DI water was compared to CuO nanofluid with different tilt https://doi.org/10.37255/jme.v4i2pp071-075 www.smenec.org 72 © SME angels 45 0 orientation CuO nanofluds gives better performance [5]. By increase the tilt angle improves the thermal performance [5,7] For same orientations TiO 2 and DI water have low thermal performance as compared to CuO nanofluid [6]. 60 0 tilt angle gives good thermal performance with titanium nanoparticles [10].…”
Section: Introductionmentioning
confidence: 99%